Process of Development Planning Consensus (Musrenbang) As A Means of Communication in Decision-Making in Siniu Subdistrict Parigi Moutong Regency - Hairudin Hairudin; Rachmat Kriyantono; Darsono Wisadirana (Wacana Journal of Social and Humanity Studies, 2017)
The function of Musrenbang in development as a means of communication of society to participate in decision-making applies in Siniu Subdistrict, Parigi Moutong Regency. The purposes of the research are, first, to explain and analyze how the process of Musrenbang become as a means of communication in the village administrative in delivering a suggestion; and third, to know and explain whether the decision-making has been re-communicated first before it goes back to the community. This research uses descriptive qualitative with data collection method through interviews and observations. The research results are: (1) the implementation of Musrenbang as a means of communication in its practice is only a formality starting from the Hamlet, Village, Subdistrict to Regency even though in its implementation is in accordance with the applicable regulations. It is proved by  the absence of Regional Medium-Term Development Plan (RPJM) as the result of Musrenbang’s implementation; (2) The implementation of Musrenbang in Siniu Subdistrict only become as a means of communication between the village administrative which only provides and accommodates the needs of society’s priority suggestions. However, the suggestion does not being delivered properly to the Regency Government. (3) The absence of re-communication made by the sub-district’s representative upon the achieved results on the society. It makes the society do not understand about the realization of the implemented development. So that Musrebang is only a medium that accommodates only the society’s aspiration via communication and does not being involved in the decision-making process.